Angioneurotic edema: report of two cases - Chaitra T.R. Telgi; Ravishankar .T.L. Telgi; Triveni Mohan Nalawade (Universidade Estadual de Campinas, 2015)
Pediatric angioedema exhibits a different cause and clinical manifestations than does adult angioedema. Unlike angioedema in adults, pediatric angioedema is caused mostly due to food, followed by insect bites, infection and antibiotics. Reactions to insect stings, both allergic and toxic, are commonly seen in medical pediatric practice but uncommonly encountered by pediatric dentists. Here we present two cases of angioedema involving the face mainly in children who presented insect bite in the affected region. Treatment and case resolution are described.